Urban vegetation structure and composition influence pedestrian thermal comfort in public spaces: A case study in Munich - Nayanesh Pattnaik; Mohammad A. Rahman; Stephan Pauleit (Urban Forestry & Urban Greening, 2025)

Branch biomass allometries for urban tree species based on terrestrial laser scanning (TLS) data - Leila Parhizgar; Nayanesh Pattnaik; Hadi Yazdi; Shu Qiguan; Stephan Pauleit; Mohammad A. Rahman; Ferdinand Ludwig; Hans Pretzsch; Thomas Rötzer (Trees, 2025)
Key message Developed species-specific allometric equations using terrestrial laser scanning (TLS). Found significant species-specific differences in branch biomass allocation. Introduced a non-destructive method for estimating urban tree biomass. Abstract Urban trees contribute to climate change adaptation by providing multiple ecosystem services, including carbon sequestration. Yet accurate information about above-ground biomass, particularly branch biomass, is scarce. This study aimed to develop allometric models for estimating branch biomass for ten common European urban tree species using terrestrial laser scanning (TLS) and quantitative structure models (QSM) data. Conducted in Munich, the study analyzed 3,283 trees, using structural variables such as diameter at breast height (dbh), height, and crown diameter. The dbh of trees in the dataset reached up to 0.8 m, with mean above-ground biomass ranging from 550 to 1.496 kg C, and branch biomass from 32.2 to 164.5 kg C. The results confirmed that dbh was the strongest predictor of branch biomass (r = 0.69–0.9), and adding height improved model accuracy ( R 2 = 0.69–0.93). Species-specific models revealed significant variations, with R. pseudoacacia showing the highest branch biomass when standardized by tree height, and P. nigra 'italica' the lowest. Conversely, when standardized by dbh, P. acerifolia showed the highest branch biomass and C. betulus the lowest. Comparisons with established forest tree models revealed that the developed allometric models tend to underestimate branch biomass for most species, with deviations ranging from 1 to 36%, reflecting unique growth forms and urban environmental conditions. The study highlights the need for species-specific allometric models to improve assessments of ecosystem services provided by urban trees.